Risk Management Strategy of Sharia Microfinance Institutions Challenges, Innovation, and Sustainability in the Era of Digital Disruption - Siswadi Siswadi; Wilda 'Ainun Najihah (Al Wajiz: Journal of Sharia and Economics Studies, 2025)
Sharia Microfinance Institutions (MFIs) have an important role in supporting the community's economy, especially in developing countries such as Indonesia. LKMS exists as an alternative financing based on sharia principles and aims to increase financial inclusion for small and medium community groups. However, in its operations, MFIs face various risks, including credit risks, liquidity risks, and operational risks that can affect the sustainability of the institution. This study aims to examine the implementation of risk management in MFIs using a qualitative approach through a literature study. The results of the study show that the implementation of risk management is able to help MFIs minimize potential losses, strengthen financial stability, and increase institutional competitiveness. However, there are challenges in the form of limited resources, lack of managerial expertise, and regulatory complexity that often hinder the effectiveness of risk management. In addition, the application of technological innovations, especially Artificial Intelligence (AI), is considered to be able to support the effectiveness of risk management through improving transaction security, service efficiency, and financing risk control. This study recommends the need to strengthen the capacity of human resources, adaptive regulatory support, and the use of digital technology to strengthen the sustainability of MFIs in the face of global economic dynamics.